Evaluación de la influencia de la motivación en el desempeño laboral del personal administrativo de la Pontificia Universidad Católica del Ecuador - Ibarra - Barahona Maldonado, Víctor Adonnys (2023)
This study aims to design and build strategies for the influence of motivation on job performance at the Pontifical Catholic University of Ecuador Ibarra campus. To achieve the objectives, motivation and job performance were analyzed through Likert-type surveys that were delivered to the staff. administrative (115) of the University. Six variables were analyzed: Organizational Commitment, Labor Motivation, Personal Conditions, Work Characteristics, Interpersonal Relations and Personnel Policies. For data analysis, the Sperman correlation coefficient was used. In this way, the percentage of influence of motivation on work performance was determined, and it was possible to design strategies to strengthen these variables. Organizational commitment and personal conditions are the variables that stand out at the Pontifical Catholic University of Ecuador Ibarra campus according to the analysis and results obtained. Since all the variables are in a very low positive correlation, they need that plus to improve them and continue to increase their perception.